2022
DOI: 10.2147/ccide.s362801
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nonsurgical Periodontal Therapy on Serum Levels of Dickkopf-Related Protein-1 in Smokers and Nonsmokers with Periodontitis: A Prospective Comparative Study

Abstract: This study aimed to evaluate and compare Dickkopf-related protein-1 (DKK1) serum levels and periodontal clinical parameters of smokers and nonsmokers with periodontitis at baseline and after nonsurgical periodontal treatment. Patients and Methods: A prospective comparative study was conducted among 24 patients with periodontitis who were divided according to the smoking habits into two groups: nonsmokers (G1) and smokers (G2). All the participants were assessed clinically by recording the probing depth (PD), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“… 28 As it had been showed improvement in periodontal condition and reduced DKK1 serum levels after in response to effective nonsurgical periodontal treatment. 27 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 28 As it had been showed improvement in periodontal condition and reduced DKK1 serum levels after in response to effective nonsurgical periodontal treatment. 27 …”
Section: Introductionmentioning
confidence: 99%
“…26 In the same direction, Azab et al showed a significant increase in the production of "DKK1 mRNA" in chronic periodontitis. 27 In the same direction, Some glycoprotein (RANKL/OPG ratio) that regulates bone metabolism had been also linked with the severity of periodontal disease conditions. 28 As it had been showed improvement in periodontal condition and reduced DKK1 serum levels after in response to effective nonsurgical periodontal treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation